Early Dendritic Morphogenesis of Adult-Born Dentate Granule Cells Is Regulated by FHL2 - Ahamad, Afrinash; Wang, Jia; Ge, Shaoyu; Kirschen, Gregory W. (Frontiers in Neuroscience, 2020)
Dentate granule cells (DGCs), the progeny of neural stem cells (NSCs) in the sub-granular zone of the dentate gyrus (DG), must develop and functionally integrate with the mature cohort of neurons in order to maintain critical hippocampal functions throughout adulthood. Dysregulation in the continuum of DGC development can result in aberrant morphology and disrupted functional maturation, impairing neuroplasticity of the network. Yet, the molecular underpinnings of the signaling involved in adult-born DGC maturation including dendritic growth, which correlates with functional integration, remains poorly understood. Given the high metabolic activity in the dentate gyrus (DG) required to achieve continuous neurogenesis, we investigated the potential regulatory role of a cellular metabolism-linked gene recently implicated in NSC cycling and neuroblast migration, called Four and a half LIM domain 2 (FHL2). The FHL2 protein modulates numerous pathways related to proliferation, migration, survival and signal transduction in peripheral tissues, interacting with machinery of the sphingosine-1-phosphate pathway, also known to be highly active especially in the embryonic hippocampus. Yet, the potential relevance of FHL2 to adult-born DGC development remains unknown. To elucidate the role of FHL2 in DGC development in the adult brain, we first confirmed endogenous expression of FHL2 in the DG, then engineered viral vectors for genetic manipulation experiments, investigating morphological changes in early stages of DGC development. While overexpression of FHL2 during early DGC development resulted in marked sprouting of dendrites, silencing of FHL2 stunted dendritic arborization. Together, these findings suggest a novel role of FHL2 in adult-born DGC morphological maturation, which may open up a new line of investigation regarding the relevance of this gene in physiology and pathology of the hippocampus such as mesial temporal lobe epilepsy (MTLE).